10-3y=6

Simple and best practice solution for 10-3y=6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10-3y=6 equation:


Simplifying
10 + -3y = 6

Solving
10 + -3y = 6

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-10' to each side of the equation.
10 + -10 + -3y = 6 + -10

Combine like terms: 10 + -10 = 0
0 + -3y = 6 + -10
-3y = 6 + -10

Combine like terms: 6 + -10 = -4
-3y = -4

Divide each side by '-3'.
y = 1.333333333

Simplifying
y = 1.333333333

See similar equations:

| 8u=7u+1 | | 18-13=1/2a=3/4a-5/8a | | 2z/7-2=7 | | 8y+4-6y=8+y+1 | | -8y-20=5y-20 | | -10q=-9q+6 | | Y=9+-0.5x | | 1/3(6n-9) | | -2(x-3)=x+24 | | 7xblank=84 | | 2(3y+5)=5(y+1) | | 36=I^2*9 | | 6x+-2(x+4)=12 | | 9-1(-1-3y)=4+y-(3-y) | | -2x-6=x+24 | | 4y+3y=2 | | 27=-9/11y | | log(x+6)= | | 5x-6=8x+3 | | Y=x(x-8) | | 4a-9whena=7 | | 143=c | | 2+y=-28 | | Z/7-9=4 | | -3/5x=17/15 | | -6x+2(x+4)=12 | | 16=4w+2-2 | | -10-5v=-10v | | .5x+0.1=0.6-(-5) | | -10-5v=10v | | x^3-18x^2+105x=0 | | 8.27/lg10 |

Equations solver categories